Multidimensional poverty index of northeast Brazil: an analysis in the period 2009-2015 (Research, Society and Development, 2021)
The present study aims to measure the multidimensional poverty level of the northeastern states from 2009 to 2015. As an empirical strategy we adopt the creation of the Multidimensional Poverty Index of the Northeast - IPMNE of the northeastern states. To this end, it uses the methodology built by Bourguignon and Chakravarty (2003), adapted by Silva et al (2016). For the construction of the IPMNE, we use the data from the National Household Sample Survey (PNAD) from the respective years. The results of the six dimensions show a reduction in the proportion of the multidimensional poverty of the northeastern population. However, three deserve greater attention: (i) Education; (ii) Communication and Information and (iii) Work and Demography. Regarding the isolated analyzes of the metropolitan, urban and rural regions, it was found that poverty was more intense in the rural area. Therefore, the present study can be used to help future public income redistribution policies of the Northeast Region.